Penguatan Literasi Alam Kampung Ilmu Purwakarta - Amie Primarni (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
The government's biggest homework now is how to improve remote areas, especially education issues. However, some groups have initiatives in building their own literacy centers in remote areas. It is a "Village of Science" in Cisarua Village, Tegalwaru District, Purwakarta Regency, West Java. located between Mount Bongkok and Mount Parang. The distance from the city center of Purwakarta is a 2 hour drive through the Jatiluhur toll gate in Purbaleunyi. This village mostly has junior high school graduates, but in the hands of a husband and wife couple, Imam B. Prasodjo and Gita Prasodjo the area is now one of the centers of literacy civilization in Purwakarta. Through the World Conscience Foundation, Together with the team of the Indonesian Writers Institute, Chairman Bambang Trim, the author was assigned to contribute to SDN students in Purwakarta to develop students in literacy, as well as to develop the ability of teachers to assist students in literacy. The activities carried out are providing assistance in terms of reading and writing, both for teachers and students. In this activity, it was seen that the enthusiasm of students and teachers was very high in improving their literacy skills.